COVID-19 in long-term care facilities in Frankfurt am Main, Germany: incidence, case reports, and lessons learned - Heudorf, Ursel; Müller, Maria; Schmehl, Cleo; Gasteyer, Stephanie; Steul, Katrin (German Medical Science GMS Publishing House, 2020)
Abstract: As of August 30, 2020, the World Health Organisation (WHO) reported 24,822,800 COVID-19 infections world wide. Severe disease and deaths occur especially in older people with chronic illnesses. Residents of nursing homes are considered to be the most vulnerable group. In this paper, the experiences with COVID-19 in nursing homes in Frankfurt will be presented and discussed.Materials and methods: Based on the data of the statutory reporting obligation, the reported COVID-19 cases are presented and incidences are calculated in different age groups and among residents of nursing homes. Outbreaks in various homes are described in detail based on the documentation from the public health department.Results: By August 28, 2020, 2,665 COVID-19 infections were reported in Frankfurt am Main (incidence 351/100,000 inhabitants), including 116 (4.3%) residents of nursing homes (2,416/100,000 residents). Almost half (39%) of all deaths in Frankfurt (n=69; incidence 9.1/100,000) were among nursing home residents (n=27; incidence 558/100,000 nursing home residents), with 22 of them in just one long-term care facility (LTCF). Compared to previous years, the mortality rate in nursing homes did not increase in the first half of 2020. In one home, 75% of residents tested positive for SARS-CoV-2 and 25% died; in two other homes, 6.7% and 14.1% of the residents became infected, and the mortality rate was 0.5% and 1%, resp. In the other 42 homes in the city (3,906 beds), the infection rate remained below 1% and the death rate was 0.1%.Discussion: In many countries, 30-70% of all deaths occur among nursing home residents, including Frankfurt (39%). An increase in overall mortality compared to previous years was not observed in Frankfurt as a whole or in the nursing homes in the city specifically. Due to the measures taken (monitoring of residents and staff, nursing care in protective clothing, prohibition or restriction of visits, physical distancing, isolation of infected people and quarantining of contact persons), only individual cases of COVID-19 illnesses occurred in nursing home residents in most homes and the outbreaks in the three homes could be stopped. We do not recommend regular nontargeted testing in nursing homes, but rather vigilance and the implementation of good hygiene as well as immediate targeted testing if COVID-19 is suspected in residents or staff. In order to mitigate the considerable negative effects of these measures on the residents, a good balance should be sought between infection prevention and the goal of ensuring self-determination and the residents' quality of life.